Decreased incidence of Kawasaki disease in South Korea during the SARS-CoV-2 pandemic - Oh, Kyung Jin; Lee, Sang-Yun (Frontiers in Pediatrics, 2024)
Purpose Analyzing Kawasaki disease epidemiology during the SARS-CoV-2 pandemic in South Korea using 2012–2020 National Health Insurance Service data. Methods The incidence of Kawasaki disease for 2012–2020 was investigated to identify changes in incidence after the start of the pandemic. National Health Insurance Service data from the Republic of Korea were used. Kawasaki disease was defined based on the International Statistical Classification of Diseases and Related Health Problems, the Tenth Revision diagnostic code (M30.3), and the intravenous immunoglobulin prescription code. Prescription history was collected for the following medications: intravenous immunoglobulin, aspirin, corticosteroids, tumor necrosis factor-α antagonist, clopidogrel, and anticoagulation drugs. Results The Kawasaki disease incidence per 100,000 individuals younger than 5 years was 238.9, 230.0, and 141.2 in 2018, 2019, and 2020, respectively. Regarding the incidence from 2012 to 2020, it was the highest in 2018 and decreased to 141.2 (p < 0.001) in 2020, after the start of the pandemic. In 2020, 28.3% of all patients with KD were infants, a percentage significantly higher than that of the previous year (p < 0.001). There was biphasic seasonality in the monthly Kawasaki disease incidence. The Kawasaki disease incidence was the highest in winter followed by that in early summer. Conclusion After the start of the pandemic, the Kawasaki disease incidence decreased, and the percentage of patients with Kawasaki disease aged <1 year increased. These findings provide support for the hypothesis suggesting an infectious trigger in Kawasaki disease.